Analisis Perbandingan Abnormal Return,Trading Volume Activity, dan Bid-Ask Spread Sebelum dan Sesudah Stock Split - Fahrizal Anwar; Nadia Asandimitra (BISMA (Bisnis dan Manajemen), 2018)
Stock splits or stock split is to break a piece of stock into n shares so that the new price per share after the stock split is 1 / n of the previous price.This study aims to investigate the market reaction to the announcement of the stock split the company listed in Indonesia Stock Exchange Period 2012-2013. The market reaction is indicated by the presence or absence of abnormal return differences, trading volume activity, and bid-ask spreads before and after the stock split announcement.Type of research is a study of events (event study).The study sample as many as 17 companies based on purposive sampling.Testing is done with a period of 5 days before and 5 after the announcement of the stock split.The technique of data analysis performed using paired sample t-test on abnormal returns while Wilcoxon signed ranks test on trading volume activity and bid-ask spreads.